Personal Reading Histories for Personal Reading Interest - Syofia Delfi; Jismulatif Jismulatif; Fangiana Safitri Diah (Universitas Riau, 2020)
Learners’ reading interest is developed based on personal reading histories; meaning that they have different reading experiences. The main purpose of this article is to present the research finding about the participant’s personal reading histories developing her reading interest. This is a Case Study by using document of Exploring Personal Reading Histories and interview for its instrument. The study found that the participant was introduced to reading through playing with words and numbers. After being able to read, she listened to stories indicating that stories are as the construction of words. The finding shows that the participant’s reading histories develop her reading interest by recognizing reading through interesting ways, media, and guidance. These The contribution of this study is the need of the implementation of Exploring Personal Reading Histories in Extensive Reading course in order to know how learners are interested in reading as well as to remind them with their meaningful reading experiences.